World Economic Outlook, April 1988. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1988)
The paper describes developments in the world economy during 1987-88, and discusses considerations underlying the IMF staff's short-term projections. The paper highlights that although the world economy is continuing to expand at a moderate pace, the persistence of large fiscal and external imbalances clouds the international economic outlook. An important positive development in 1987 was the strengthening of policy coordination among the major industrial countries. The paper assesses the policy issues facing the industrial countries, against the background of alternative scenarios of medium-term developments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet